Plasma properties of suprathermal electrons near comet 67P/Churyumov-Gerasimenko with Rosetta - Myllys,M; Henri,P; Galand,M; Heritier,KL; Gilet,N; Goldstein,R; Eriksson,A; Johansson,F; Deca,J (Astronomy and Astrophysics: a European journal, 2019)
Context. The Rosetta spacecraft escorted comet 67P/Churyumov-Gerasimenko from 2014 to September 2016. The mission provided in situ observations of the cometary plasma during different phases of the cometary activity, which enabled us to better understand its evolution as a function of heliocentric distance.Aims. In this study, different electron populations, called warm and hot, observed by the Ion and Electron Sensor (IES) of the Rosetta Plasma Consortium (RPC) are investigated near the comet during the escorting phase of the Rosetta mission.Methods. The estimates for the suprathermal electron densities and temperatures were extracted using IES electron data by fitting a double-kappa function to the measured velocity distributions. The fitting results were validated using observations from other RPC instruments. We give upgraded estimates for the warm and hot population densities compared to values previously shown in literature.Results. The fitted density and temperature estimates for both electron populations seen by IES are expressed as a function of heliocentric distance to study their evolution with the cometary activity. In addition, we studied the dependence between the electron properties and cometocentric distance.Conclusions. We observed that when the neutral outgassing rate of the nucleus is high (i.e., near perihelion) the suprathermal electrons are well characterized by a double-kappa distribution. In addition, warm and hot populations show a significant dependence with the heliocentric distance. The populations become clearly denser near perihelion while their temperatures are observed to remain almost constant. Moreover, the warm electron population density is shown to be strongly dependent on the radial distance from the comet. Finally, based on our results we reject the hypothesis that hot electron population seen by IES consists of solely suprathermal (halo) solar wind electrons, while we suggest that the hot electron population mainly consists of